Asymmetric synthesis of tetrahydroquinolin-3-ols via CoCl2-catalyzed reductive cyclization of nitro cyclic sulfites with NaBH4 - Jagdale, Arun R.; Reddy, R. Santhosh; Sudalai, Arumugam (Organic Letters, 2009)
A new method for the construction of chiral 3-substituted tetrahydroquinoline derivatives based on asymmetric dihydroxylation and CoCl2-catalyzed reductive, cyclization of nitro cyclic sulfites with NaBH4 has been described with high optical purities. This method has been successfully applied in the formal synthesis of PNU 95666E and anachelin H chromophore.